DEVIDEND PAY OUT RATIO PADA EMITEN MANUFAKTUR DI BURSA EFEK INDONESIA - Dionysia Kowanda; Rowland Bismark Fernando Pasaribu; Dian Indah Sari (Fakultas Bisnis UKDW, 2017)
AbstractThis study aims to analyze and empirically test the significance of partial and simultaneous effect ofinsider ownership, DER, ROE, firm size, IOS, PER, and EPS Dividend Payout Ratio (DPR) inmanufacturing companies in Indonesia Stock Exchange of 2008 - 2013 period. The results showedthat partially turned out just ROE, IOS, PER, and EPS significantly influence of dividend payoutratio, while the insider ownership, DER, and firm size does not affect significant. Meanwhilesimultaneously, all variables INSDOWN, DER, ROE, FSIZE, IOS, PER, EPS significantly influenceDPR. From coefficient of determination can be concluded that the ability of Insider Ownership, DER,ROE, Firm Size, IOS, PER and EPS in explaining dividend payout ratio amounted to 71.1 per centwhile the remaining 28.9 per cent influenced or explained by other variables not used in this study.Keywords: insider ownership, firm size, investment opportuinity set, earning per share, dividendpayout ratio